PENGARUH KEMAMPUAN KERJA, STRES KERJA DAN ETOS KERJA TERHADAP KINERJA KARYAWAN - Made Siska Dwi Jayanthi; Ni Nyoman suryani (STIMI Handayani Denpasar, 2018)
This research aims to find out and analyze the influence of work ability, work stress and work ethic are partial or simultaneous performance against CV Waja Motor Blahbatuh using 50 samples (all employees). Technical analysis is the Study of the instrument Test (test validity, Reliability Test), a classic Assumption Test (test of Normality, test Multicollinearity Test, Heteroskedasitas), test the hypothesis (Multiple Linear regression analysis, Correlation Analysis of multiple Determination, analysis, test, test t) F. Research results based on multiple regression analysis of acquired patterns of positive influence the ability of work and work ethic against the performance of the employees and the pattern of negative influences of work stress on performance of employees. F test results show that Fhitung registration (24.607). Therefore Fhitung is greater than Ftabel (2.84) means the simultaneous work ability, work stress and work ethic of significant effect on performance of employees. T test results for variable working ability obtained thitung (2.491) greater than ttabel (2.021), means the ability of a significant effect on performance of work of employees. To work stress variables obtained thitung (-2.221) greater than ttabel (-2.021), mean work stress and significant effect on performance of employees. And for variable work ethic earned thitung (2.714) greater than ttabel (2.021), meaning influential work ethic and significantly to the performance of the employee.